22. AN INVESTIGATION OF THE CHANGE IN KNEE PAIN THRESHOLD FOLLOWING AURICULAR ACUPRESSURE AT THE KNEE, SHENMEN, SUBCORTEX, SYMPATHETIC ACUPOINTS ON THE LEFT SIDE IN HEALTHY VOLUNTEERS (Vietnam Journal of Community Medicine, 2024)
Objectives: Investigate the change in knee pain threshold on both sides following auricular acupressure at the knee, shenmen, subcortex, sympathetic acupoints on the left side in healthy volunteers.Subject and methods: This is an interventional before-and-after pilot study on 28 healthy volunteers. The study was conducted at Lab of acupuncture research at the Faculty of Traditional Medicine, University of Medicine and Pharmacy at Ho Chi Minh City from February 2023 to May 2023. Eligible participants had Vaccaria ear seeds applied to the knee, shenmen, sympathetic, and subcortex acupoints on the left ear, with continuous pressure for five minutes to elicit deqi sensation. The pain thresholds were measured using the Multi-capacity Digital Force Gage FDIX. The differences in the pain thresholds before and after the intervention were recorded at 12 locations on both knees, corresponding to nerve segments.Results: The differences in pain thresholds at the locations corresponding to the L3, L4, L5, S1, and S2 nerve segments before and after auricular acupressure on the knee, shenmen, sympathetic, subcortex acupoints on the left ear were statistically greater in the left knee than in the right knee (p
Keywords: Auricular acupressure, knee, shenmen, subcortex, sympathetic, pain threshold